التجارة الالكترونية طريق أساسي لتحقيق التنمية - بريكة, السعيد (Sciences humaines, 2014)
التجارة الالكترونية أداء لأعمال مختلفة أكثر من كونها قضية أتمتة، وبغض النظر عن مستويات التكلفة وتعقيدات عملياتها فإنها مبنية على حاجات الأعمال، وعلى دورها في تحسين عمليات المحاسبة الالكترونية وكذا إدارة السجلات. ولقد تبين من خلال التجهيزات التي استلمت عند شيوع استخدام الانترنيت؛ كيف أدى هذا الأخير إلى تخفيض تكلفة فترة التخزين وسرعت وفعالية تقديم الخدمات للزبائن، مثل: خدمة المصرف على الخط من خلال دفع الفواتير الكترونيا، تحويل ونقل وإدارة قائمة الرواتب. الشيء الذي حسّن من كفاءة العمل، لذلك لجأت أغلبية المؤسسات المالية إلى عرض هذه الخدمات، وبفضل التجارة الالكترونية لم تحصر في العمل لوحده لكنها تشترك وقطاع الاتصالات والإعلام في الهاتف والتلفاز والدفع الالكتروني، وإن ما يميز الانترنيت هو قدرة المنتجين على بيع المنتجات وبسهولة تامة لزبائنهم أو المشترين دون الحاجة إلى وسطاء. من خلال هذه الورقة نناقش التجارة الالكترونية كطريق أساسي لتنمية المعاملات الإقتصادية   E-commerce is a performance of different actions, rather than a technical issue, or  an Automation, irrespective of their levels of cost and complexity of its operations are based on the needs of business, not to mention its role in improving the accounting processes, as well as electronic records management. It is clear from the equipment received at the prevalence of use of the Internet; how the latter has led to a reduction in the cost of storage and accelerated the effective delivery of services to customers, such as: on-line service of the bank through the payment of invoices electronically, conversion, transfer and management of the salary. This has which improved the efficiency of work, so resorted to the majority of financial institutions to offer such services. As a concequence,  electronic commerce was not confined to work alone, but involved the communications sector and the media on the phone, television and electronic payment. As a distinctelement, internet gave producers the opportunity to sell products easily and fully to their customers or buyers, without need for intermediaries. The aim of this paper is it highly that electronic commerce as a basic process to surge the economic transactions.